PUPIL CYCLE TIME AND PERIPAPILLARY PERFUSION IN ANGLE CLOSURE GLAUCOMA: Oral Presentation - Observational Study - Resident - Kamal, Muhammad Alfin; Rahmi, Fifin Luthfia; Puspasari, Denti; Cahyono, Maharani (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesOne of important roles in the pathogenesis of glaucoma is vascular condition. To enhance glaucomamanagement, the clinical assessment of ocular perfusion is required. The pupillary light reflex'safferent or efferent pathways may become impaired as a result of pupil cycle time (PCT) elongation.PCT is a simple objective method to measure the function of optic nerve, including glaucoma. Thepurpose of this study is to evaluate the connection between pupil PCT and peripapillary perfusion. MethodsA cross-sectional study from Kariadi Hospital included 26 eyes with angle closure glaucoma and 26eyes of healthy patients. Complete ophthalmologic examinations, PCT measurements, and OCTperipapillary angiography were performed on each patient. Patients with history of drugs use thatcan affect pupillary reflexes such as barbiturates, methyldopa, anaesthetics, and antidepressant, andpatients with history of glaucoma attack are excluded. The comparisons between the two groupswere examined, with a p<0.05 indicating statistical significance. ResultsThe mean PCT of normal subjects was 943,4ms (882,4ms – 993,4ms) and angle closure glaucomasubject was 1789,5ms (1060ms – 4600ms). There were statistically significant difference of PCTvalue in angle closure glaucoma compared to normal subjects (P<0,05). Peripapillary flow index andperipapillary vessel density in closed angle glaucomatous eyes were lower than normal eyes(P<0.05). There is a significant relationship between PCT with peripapillary flow index andperipapillary vessel density. (P<0,05). ConclusionIn angle closure glaucoma, prolonged PCT associated with decreased peripapillary perfusion asshown by decreases in peripapillary flow index and peripapillary vascular density.